The Greeks and the British in the Levant, 1800-1960s
1 online resource (xxi, 343 pages)
Keywords: “This book explores the concept of 'the Levant' as a component of the regional and international system during the age of imperialism. At its heart is a focus on the experience of Greek-speaking societies and, above all, the independent state of Greece that came into existence in 1830. A key sub-theme running through the account is the Anglo-Hellenic connection stemming from an enhanced British presence in the Eastern Mediterranean from the 1830s and 1840s, and in particular its relationship to the Greek polity. Within this framework the emergence of the idea of 'Greater Greece' is integrated into the narrative, including its regional reverberations and ethnic tensions. Other contributions examine trade and finance, gender issues, colonialism and the distinctive experience of Cyprus. The core of the volume deals centrally with three interlocking themes: modernity, nationalism and trans-nationalism. Ultimately these forces were to prove at odds with the ambiguity and elite structures that characterized the Levant in its nineteenth-century heyday. The book analyses the evolution, and increasing definition from the late 1950s, of Greece's modern European identity, while taking into account the magnetic force of other relationships and regional links. This treatment connects with the choices and dilemmas facing Greece and its surrounding region, which contemporary crises invariably throw into relief. It will be of interest both to specialised historians and students of current affairs seeking to understand the broader historical context“--Provided by publisher.